Progesterone Pre-Synchronization in Nellore Females Submitted to a Fixed-Time Artificial Insemination (FTAI) Program - Silva dos Santos, Wendel Denian; Moreira Maciel, Maria Antônia; Gomes do Amaral, Raquel; Azevedo Menezes, Artur; Galvão Loiola, Marcus Vinícius; Freitas Bittencourt, Rodrigo; de Lisboa Ribeiro Filho, Antonio; Oliveira Brandão, Tiago; Soares Rodrigues , Alexandra (Acta Scientiae Veterinariae, 2024)
Background: The development of Fixed-Time Artificial Insemination (FTAI), has emerged to reduce the factors that compromise success in conventional AI. However, on average, 50% of the females synchronized for FTAI conceive in the first service postpartum. Thus, the present study aimed to evaluate the effect of pre-synchronization with injectable P4 on follicular and luteal morphofunctional parameters, as well as the fertility rates of acyclic and lactating Nellore females, submitted to a FTAI program. Materials, Methods & Results: On a random day, referred to as day -10 (D -10), 42 Nellore females were randomly divided into 2 treatments: Group P4i (n = 23) - 150 mg of long-acting injectable progesterone was administered intramuscularly (IM) and Control Group (n = 19) - 1 mL of saline solution IM was administered. On day zero (D0), an intravaginal device containing 1.0 g of progesterone was inserted, associated with the application of 2.0 mg of estradiol benzoate intramuscularly (IM). On day eight (D8) the removal of the intravaginal progesterone devices was performed, animals received 500 μg of cloprostenol sodium (IM), 300 IU of chorionic gonadotropin and 1mg of estradiol cypionate (IM). The evaluations of the follicular diameter (FOLD), the area of the follicular wall (FOLA) the blood perfusion area of the follicular wall (FOLV) and percentage of vascularity in the follicular area (%FOLV) were performed on D10 of the synchronization protocol, by B-mode ultrasonography and colour Doppler, before carrying out artificial inseminations. The evaluations of the luteal diameter (CLD), the total luteal area (CLA), and blood perfusion area CL (CLV), and percentage of vascularity in the corpus luteum area (%CLV) and ovulation rate were performed on D23. The diagnosis of pregnancy was carried out by transrectal ultrasonography on D40, using a 5.0MHz linear transducer. The data were processed by the Statistical Package for Social Science (SPSS, version 19) 2 with a 5% significance level. The Control Group showed mean values of FOLD, FOLA, FOLV and %FOLV equivalent to the values presented by the P4i Group, no significant difference was observed between the groups. In the evaluation of the morphofunctional parameters of the corpus luteum (CL), similar mean CLD, CLA, CLV and %CLV were found for the Control and P4i groups, no significant difference was observed between the data. As for the ovulation rate, the control group showed 84.2% and the P4i group 87.0%, with no difference between them (P > 0.05). The conception rate was 36.8% in the control group and 50.0% in the P4i group. Despite the positive numerical difference found in the conception rate for the P4i group, there was no statistical difference between the variables analyzed. Discussion: The follicular and luteal morphofunctional characteristics and ovulation rate found in this experiment, were not affected by pre-synchronization with P4i before the start of the ovulation synchronization protocol for FTAI, proving similar to the results found by other authors, since it was hypothesized that pre-synchronization with injectable progesterone in anoestrous females, could cause sensitization in the mid-basal region of the hypothalamus to estrogen and allow re-establishment of the GnRH secretion pattern, and LH pulsatility, consequently favouring follicular growth and ovulation, with the formation of greater CL size, favouring the establishment of gestation and an increase in fertility rates. It is concluded that pre-synchronization with injectable progesterone 10 days before the start of the synchronization protocol for FTAI, was unable to influence follicular and luteal morphofunctional parameters and ovulation rate, however, there was a numerical increase in the conception rate for the P4i group. Keywords: corpus luteum, doppler, fertility, FTAI. Título: Pré-Sincronização com progesterona em fêmeas nelore submetidas a um programa de inseminação artificial em tempo fixo (IATF) Descritores: corpo lúteo, doppler, fertilidade, IATF.